Investigating the utility of hyperspectral sounders in the 9.6 μm band to improve ozone analyses. (12th November 2021) - Karpowicz, Bryan M.; McCarty, Will; Wargan, Krzysztof
Abstract: Hyperspectral sounder brightness temperatures assimilated in the Global Earth Observing System Atmospheric Data Assimilation System (GEOS‐ADAS) were previously limited to assimilating temperature and moisture. The ozone‐sensitive 9.6  μ m region is sensed by several hyperspectral sounders including AIRS (Atmospheric InfraRed Sounder), IASI (Infrared Atmospheric Sounding Interferometer), and CrIS (Cross‐track Infrared Sounder). Direct assimilation of brightness temperatures in the 9.6  μ m region have been operational at ECMWF for several years. With this study, similar improvements using the GEOS‐ADAS are presented. Channels were selected from available operational subsets evaluating information content and minimizing inter‐channel correlation. Additionally, information such as channel selections made by other studies, and vertical sensitivities of ozone and temperature were considered. The analyses produced show improvements verified against ozonesondes taken from SHADOZ (Southern Hemisphere Additional Ozonesondes) and WOUDC (World Ozone and Ultraviolet Data Center). This work will be added to the GEOS‐ADAS and will provide an improved source of ozone data in NASA Global Modeling and Assimilation Office products. Abstract : Hyperspectral sounder brightness temperatures assimilated in the Global Earth Observing System Atmospheric Data Assimilation System (GEOS‐ADAS) were previously limited to assimilating temperature and moisture. The ozone‐sensitive 9.6  μ m region is sensed by several hyperspectral sounders including AIRS, IASI, and CrIS, and are directly assimilated to produce an improved ozone analysis verified against available ozonesondes. Improvements in tropical ozone is particularly notable including an improvement in tropical wave‐one representation in the analysis.